Introduction to Multicopter Design and Control - Quan, Quan.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book is the first textbook specially on multicopter systems in the world. It provides a comprehensive overview of multicopter systems, rather than focusing on a single method or technique. The fifteen chapters are divided into five parts, covering the topics of multicopter design, modeling, state estimation, control, and decision-making. It differs from other books in the field in three major respects: it is basic and practical, offering self-contained content and presenting hands-on methods; it is comprehensive and systematic; and it is timely. It is also closely related to the autopilot that users often employ today and provides insights into the code employed. As such, it offers a valuable resource for anyone interested in multicopters, including students, teachers, researchers, and engineers.
Introduction -- PART I DESIGN -- Basic Composition -- Configuration and Structural Design -- Modeling and evaluation of propulsion system -- PART II MODELING -- Coordinate system and attitude representation -- Dynamic model and parameter identification -- PART III ESTIMATION -- Sensor model and calibration -- Observability and Kalman filter -- State estimation -- PART IV CONTROL -- Stability and Controllability -- Low-Level Flight Control -- Position Control based on SemiAutonomous Autopilot -- PART V DECISION -- Mission Decision-Making -- Health Evaluation and Failsafe -- Outlook.
Keywords: Control engineering; Robotics; Automation; Aerospace engineering; Astronautics; Control, Robotics, Automation; Control and Systems Theory; Aerospace Technology and Astronautics